ANALISIS PENGGUNAAN METODE INQUIRY LEARNING UNTUK MATERI IPA DI KELAS VIII SMP NEGERI 2 ARAMO - Kasihani Hia, Kristina (Universitas Nias Raya, 2025)
The aim of the research is to find out how the inquiry learning method works, student activities after using the inquiry learning method, student learning motivation, and what the learning outcomes of students in class VIII SMP Negeri 2 Aramo are. This type of research is qualitative research. Data collection techniques are observation and interviews accompanied by taking photos as evidence of existing research results. The results of the research show that class VIII students at SMP Negeri 2 Aramo in inquiry learning play the role of seeking and finding their own answers to a problem given by the teacher. Student activities in the inquiry learning process are: carrying out orientation activities, problem formulating activities, hypothesis formulating activities, data collecting activities, and conclusion formulating activities. The learning motivation of students in class VIII SMP Negeri 2 Aramo is to achieve learning goals and to gain new experiences through the learning process. Learning outcomes are the abilities of students in class VIII of SMP Negeri 2 Aramo obtained after learning activities. The results of the analysis obtained by researchers when conducting research in the field were the grades of class VIII students at SMP Negeri 2 Aramo with an average score of 87% (standard). It can be concluded that the science subject teacher in class VIII of SMP Negeri 2 Aramo has implemented the inquiry learning method during the learning process. Suggestions (1) For science-biology subject teachers in class VIII of SMP Negeri 2 Aramo, the current performance is very good and the hope is that in the future it will be even better. (2) For students in class VIII of SMP Negeri 2 Aramo, by paying attention and adapting their learning style to the methods applied by the teacher, they can improve good learning outcomes, they can also be good listeners to gain more knowledge, both within the school environment. and outside of school, and gain achievements and success in their achievements. (3) For other researchers, this research can be used as a reference for researchers who will conduct similar research, so that the research results can be more complete and accurate.